Alcohol and Violence: A Field Experiment with Bartenders in Bogotá,Colombia (2019)
This paper studies whether bartenders that adopt standardized practices can promote responsible alcohol consumptionand subsequently reduce alcohol-attributable violence. We conduct a randomized experiment in four localities of Bogotá in cooperation with Colombia's largest brewery and Bogotá's Secretariat of Security, Coexistence, and Justice. Ourdesign allows estimating direct and spillover effects on reported incidents within and around bars. Results show thatbartenders in treatment locations sell more water and food, thus contributing to more responsible alcohol consumptionby patrons. We find no direct or spillover effects of these changes in consumption on brawls, but some improvement onother alcohol-related incidents.